Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c8cc07981a
|View full text |Cite
|
Sign up to set email alerts
|

A clickable caging group as a new platform for modular caged compounds with improved photochemical properties

Abstract: A clickable caging group was designed, which was applied to the synthesis of caged paclitaxels with improved physical and photochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“… 459 The bis(carboxymethoxy) moiety of 48b conferred increased water solubility (up to 2.7 mM in acetonitrile/HEPES buffer 5:95, pH 7.2). 367 The dialkylaminomethyl C8 substituents of 49a – d ( Table 9 ) significantly reduced the acidity of the 7-OH group in 49c (p K a = 4.9) 460 and 49d (p K a = 3.8) 461 relative to the parent 40a (p K a = 6.2), presumably because the aminomethyl group forms an intramolecular hydrogen bond with the phenolic hydroxyl group, 462 leading to greater photouncaging efficiency at the lower end of the physiological pH range. The liberation of carboxylic acids, diols, amines (as carbamic acids), and phenols (as carbonic acids) from 49a – d occurred with quantum efficiencies similar to or slightly exceeding that for 40a upon both 1P (Φ r = 0.06–0.014, λ irr = 360 nm) and 2P excitation (δ unc = 0.5–1.4 GM, 755 nm).…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“… 459 The bis(carboxymethoxy) moiety of 48b conferred increased water solubility (up to 2.7 mM in acetonitrile/HEPES buffer 5:95, pH 7.2). 367 The dialkylaminomethyl C8 substituents of 49a – d ( Table 9 ) significantly reduced the acidity of the 7-OH group in 49c (p K a = 4.9) 460 and 49d (p K a = 3.8) 461 relative to the parent 40a (p K a = 6.2), presumably because the aminomethyl group forms an intramolecular hydrogen bond with the phenolic hydroxyl group, 462 leading to greater photouncaging efficiency at the lower end of the physiological pH range. The liberation of carboxylic acids, diols, amines (as carbamic acids), and phenols (as carbonic acids) from 49a – d occurred with quantum efficiencies similar to or slightly exceeding that for 40a upon both 1P (Φ r = 0.06–0.014, λ irr = 360 nm) and 2P excitation (δ unc = 0.5–1.4 GM, 755 nm).…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“…We previously developed Bhc caged compounds of various biologically active molecules that exhibit high photolytic efficiencies 28,45,46,47 . With the aim of expanding the repertoire of Bhc caging groups, we also reported platforms of modular caged compounds that can be modified easily by the introduction of various functional units 32,40,41 . The present protocol therefore represents a method for the synthesis of a clickable precursor of Bhc caging groups that can be modified via the copper(I)-catalyzed Huisgen cyclization.…”
Section: Discussionmentioning
confidence: 99%
“…If additional properties can be installed easily into the caging groups without compromising their photosensitivity, then the repertoire of caged compounds can be expanded 34,35,36,37,38,39 . We therefore designed modular caged compounds that comprise three parts, namely the Bhc group as a photo-responsive core, chemical handles for the installation of additional functionalities, and the molecules that are to be masked 40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous reports on photocaged taxane derivatives, [177][178][179][180] their application in delivery systems has been rarely studied. Xu et al reported such a delivery system for paclitaxel using a pyramid-shaped RNA nanocage.…”
Section: Taxanementioning
confidence: 99%